FNGR 2 | Lesson 5 | Try This! (Writing Inverse Equations) Solutions

1.  \(f(g(x)) = 2x^2-4x+1\) ; therefore  \(f\)  and  \(g\)  are not inverses.

2.  \(f(g(x)) = g(f(x)) =x\) ; therefore  \(f\)  and  \(g\)  are inverses.

3.  The function has an inverse.  \(f^{-1}(x)=\dfrac{x+1}{3}\)

4.  The function has an inverse.  \(f^{-1}(x) = \dfrac 4x \)

5.  The function does not have an inverse, it is not 1-1.

6.  The function has an inverse.  \(f^{-1}(x) = \sqrt[3]{x-1}\)


Return to Try This! (Writing Inverse Equations)

Continue to Practice (Writing Inverse Equations)